Pemberdayaan UMKM Melalui Lembaga Keuangan Syariah Sebagai Upaya Pengentasan Kemiskinan Kota Padangsidimpuan - Delima Sari Lubis (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
One way that can be done to build the local economy is through increased UMKM. Existence of UMKM simply can not be in doubt, because it has proven able to survive as an economic driver in the event of a crisis. On the other hand, has many limitations and require care and support to enable the business directional link. Problems faced UMKM in all areas is almost the same, that is; limited working capital, the quality of human resources is low, productivity and product quality is low, and the lack of mastery of science and technology.To resolve these issues, the need for a balance between the financial sector which is sufficient progress with the real sector (UMKM). in several ways, namely;First, the need for a partnership program for businesses that have not bankable,The second, in terms of management, UMKM desperately need a companion who acts as advisors to enhance capacity building.Third, the popularity of Islamic financial institutions need to be improved.